Aeromedical interhospital transport of an adult with COVID-19 on extracorporeal membrane oxygenation: case report - Vânia Paula de Carvalho; Bruno Gonçalves da Silva; Flávio Lopes Ferreira; André Alves Elias; Armando Sergio de Aguiar Filho; Nelson Miguel Galindo Neto (SciELO, 2022)
Abstract Objective: To describe the experience of aeromedical interhospital transport of an adult patient with severe hypoxemic respiratory failure due to SARS-CoV-2, on extracorporeal membrane oxygenation. Method: This is a case report, guided by the tool Case Report Guidelines, with a descriptive approach. Data were collected from the digital medical record and field notes after the approval by the Institution and the Human Research Ethics Committee. Results: The transport of a critically ill, unstable patient with acute respiratory syndrome 2 on extracorporeal oxygenation was an opportunity for the team to acquire new knowledge. The proper preparation of the fixed-wing aircraft and the profile of the team of specialist nurses contributed to the safety and quality in the three phases of flight: preflight, in-flight and post-flight. Conclusion: Air transport of adults on cardiopulmonary bypass to referral centers, under the care of an experienced multidisciplinary team, can contribute to positive results. The nurses' autonomy, their leadership role and expertise in process management are highlighted. Thus, success was evidenced with the patient's discharge after 45 days from the Intensive Care Unit.